The Spartan Twins - Perkins, Lucy Fitch, 1865-1937 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Spartan Twins" by Lucy Fitch Perkins is a children's historical novel written in the early 20th century. The story centers on the lives of twin siblings, Dion and Daphne, who are children of a Spartan farmer living on the island of Salamis, just off the coast of Greece in the 5th century B.C. The narrative captures their adventures and experiences as they navigate their family life, interactions with a visiting philosopher, and ultimately their journey to Athens. The opening of the book introduces the twins and their family, focusing on a typical spring day at their farm where Lydia, the mother, is busy preparing for an unexpected guest. The children, looking remarkably alike, are depicted as playful and lively, engaging in banter about their differing abilities and aspirations. As their father, Melas, brings home a traveling philosopher, Lydia scrambles to prepare a meal for her husband and their honored guest. The chapter sets a lively scene filled with familial warmth and hints at the twins' adventurous spirits as they engage with new people and ideas, establishing a rich context for their impending journey into the heart of Athens and its accompanying challenges. (This is an automatically generated summary.)
Release date is 2006-02-01
Produced by Charles Aldarondo, Mary Meehan and the Online Distributed Proofreading Team
Keywords: Twins -- Juvenile fiction; Greece -- History -- Juvenile fiction